2023
DOI: 10.1021/acsanm.2c05407
|View full text |Cite
|
Sign up to set email alerts
|

Review of Carbon Dot-Based Drug Conjugates for Cancer Therapy

Abstract: Carbon Dots (CDs) are a class of carbon-based nanostructure known as zero-dimensional nanomaterial and have great potential in the field of targeted chemotherapy. CDs have been extensively explored for bioimaging, sensing, and therapy due to their high quantum yield, low cytotoxicity, high water solubility, good photostability, and tunable excitation wavelength-dependent emission properties. CDs conjugated with various anticancer drugs such as Doxorubicin (DOX), Epirubicin and Temozolomide, Protoporphyrin IX (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…RCDs were prepared by the microwave method with O-phenylenediamine as the precursor. 29 TEM (Fig. 1a) showed that the average particle size was 4 AE 0.31 nm, and the lattice spacing of RCDs was d = 0.21 nm, which coincides with the graphene carbon lattice plane [100].…”
Section: Preparation and Characterization Of Cu-mof@rcdmentioning
confidence: 99%
See 1 more Smart Citation
“…RCDs were prepared by the microwave method with O-phenylenediamine as the precursor. 29 TEM (Fig. 1a) showed that the average particle size was 4 AE 0.31 nm, and the lattice spacing of RCDs was d = 0.21 nm, which coincides with the graphene carbon lattice plane [100].…”
Section: Preparation and Characterization Of Cu-mof@rcdmentioning
confidence: 99%
“…Carbon dots (CDs) are new nanomaterials with excellent biocompatibility and photothermal properties, and have great development prospects in the field of nanomedicine materials. 29,30 In this study, we designed a cancer therapeutic nano-agent Cu-metal-organic framework@red carbon dot (Cu-MOF@RCD) for stimulus-responsive enhanced immunogenicity and multimodal anti-tumor immune checkpoint blockade therapy. Porous copper metal-organic framework nanoparticles (Cu-MOF) are used as drug carriers and CDT therapeutic agents, which encapsulated red carbon dots (RCDs) to yield Cu-MOF@RCD to realize dual PDT and PTT effect.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dots (CDs) are carbon nanomaterials featured with high fluorescence stability, good biocompatibility, low toxicity, easy preparation, and wide applications, such as fluorescence imaging, biochemical analysis, photocatalysis, , and cancer therapy. , Recently, CD-based hypotoxic antimicrobial materials have drawn extensive attention from the scientific community. For instance, polyethylenimine (PEI), as a cationic polymer with many primary, secondary, and tertiary amino groups, has been popularly used in drug delivery, gene transfection, and antibacterial applications. Due to the strong penetration and disruption ability of the positively charged PEI to bacterial cell membranes, the PEI-functionalized CDs provide candidates for the fabrication of antibacterial nanomedications. However, despite very promising capabilities, some cationic CD-based antibacterial nanomedications in clinical treatment still face a critical issue that the higher concentrations are required to eliminate Gram-negative bacteria compared to that for Gram-positive bacteria, which accordingly address safety concerns. Hence, constant efforts have been devoted to improving the antibacterial efficacy of cationic CD-based antibacterial nanomedications, particularly against Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon quantum dots (CQDs) are uorescent semiconductor nanoparticles that have recently been used in pharmaceutical and biomedical analysis by measuring the enhancement or quenching of the uorescent signal from the CQDs as a result of an interaction of the CQDs with the compound of interest. [45][46][47][48][49][50] Originally, CQDs were prepared from primary chemical precursors such as citric acid, polyethyleneimine, zinc oxide, phenolic resins, and ethylene glycol, which were incompatible with concepts of green analytical chemistry. [51][52][53][54] Therefore, scientists have recently focused on nding environmentally friendly precursors from nature as substitutes, such as biomass wastes and plant-derived pharmaceuticals, because they are environmentally friendly, widely available, biocompatible, and rich in low-cost renewable raw materials (rich in C, H, N, and O atoms) such as polysaccharides, proteins, nucleic acids, and phospholipids.…”
Section: Introductionmentioning
confidence: 99%